The des-Arg9-bradykinin/B1R axis: Hepatic damage in COVID-19 - Mendes, Gabriel Moreira de M; Do Nascimento, Israel Júnior Borges; Marazzi-Diniz, Paulo HS.; Da Silveira, Izabela B.; Itaborahy, Matheus F.; Viana, Luiz E.; Silva, Filipe A.; Santana, Monique F; Pinto, Rebecca AA.; Dutra, Bruna G.; Lacerda, Marcus Vinicius G.; Araujo, Stanley A.; et al. (Frontiers in Physiology, 2022)
Patients infected by the SARS-CoV-2 virus are commonly diagnosed with threatening liver conditions associated with drug-induced therapies and systemic viral action. RNA-Seq data from cells in bronchoalveolar lavage fluid (BALF) from COVID-19 patients have pointed out dysregulation of kallikrein-kinin and renin-angiotensin systems as a possible mechanism that triggers multi-organ damage away from the leading site of virus infection. Therefore, we measured the plasma concentration of biologically active peptides from the kallikrein-kinin system, bradykinin and des-Arg9-bradykinin, and liver expression of its proinflammatory axis, bradykinin 1 receptor (B1R). We measured the plasma concentration of bradykinin and des-Arg9-bradykinin of 20 virologically confirmed COVID-19 patients using a liquid chromatography-tandem mass spectrometry-based methodology. The expression of B1R was evaluated by immunohistochemistry from post-mortem liver specimens of 27 COVID-19 individuals. We found a significantly higher blood level of des-Arg9-bradykinin and a lower bradykinin concentration in patients with COVID-19 compared to a healthy, uninfected control group. We also observed increased B1R expression levels in hepatic tissues of patients with COVID-19 under all hepatic injuries analyzed (liver congestion, portal vein dilation, steatosis, and ischemic necrosis). Our data indicate that des-Arg9-bradykinin/B1R is associated with the acute hepatic dysfunction induced by the SARS-CoV-2 virus infection in the pathogenesis of COVID-19.